Preparation method of high-conductivity graphene / copper alloy material
Patent Information
- Application Number
- CN202610161457.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-04
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-02-04
AI Technical Summary
然而,现有技术通常面临以下问题:一是石墨烯在铜基体中分散不均匀,易于团聚;二是石墨烯与铜之间的界面结合较弱,存在较多的界面缺陷和杂质,如氟化物、硼化物等,这些杂质在界面处偏聚会形成脆性相,严重阻碍电子和声子的传输,导致复合材料的电导率和热导率远低于理论值
通过壳聚糖与硼酸的协同处理,实现了对石墨烯表面氟离子和硼酸残留的高效双重净化,极大降低了界面杂质含量,避免了脆性相的形成。
Smart Images

Figure SMS_5 
Figure SMS_6 
Figure SMS_7
Abstract
Description
Technical Field
[0001] This invention relates to the field of non-ferrous metals technology, and in particular to a method for preparing a highly conductive graphene / copper alloy material. Background Technology
[0002] Graphene is considered an ideal filler for reinforcing metal matrix composites due to its excellent electrical, thermal, and mechanical properties. Graphene-copper composites are expected to significantly improve the strength and thermal conductivity of materials while maintaining high electrical conductivity, and have broad application prospects in electronic packaging, heat dissipation devices, and high-end wires.
[0003] Currently, graphene-copper composites are commonly prepared using powder metallurgy, electroless plating, or electrodeposition. However, existing technologies typically face the following problems: first, graphene is unevenly dispersed in the copper matrix and is prone to agglomeration; second, the interfacial bonding between graphene and copper is weak, with numerous interfacial defects and impurities, such as fluorides and borides. These impurities agglomerate at the interface to form brittle phases, severely hindering the transport of electrons and phonons, resulting in the electrical and thermal conductivity of the composite material being far lower than theoretical values.
[0004] Therefore, it is of great significance to develop a method for preparing highly conductive graphene-copper alloy materials that can effectively purify the graphene surface, repair its structure, and achieve strong interfacial bonding with the copper matrix, while also being process-stable and environmentally adaptable. Summary of the Invention
[0005] This application provides a method for preparing a highly conductive graphene / copper alloy material, which solves the problems existing in the prior art. This application provides a method for preparing a highly conductive graphene / copper alloy material, including the following steps: S1. Mix graphene dispersion with hydrofluoric acid solution at a volume ratio of 50:1 and sonicate for 5 minutes. Then place in a reaction vessel and keep at 170℃ for 25 hours. After cooling, filter and wash to obtain a wet filter cake. Redisperse the wet filter cake in double-distilled water, add boric acid, and stir at 55℃ for 25 minutes. Adjust the pH to 4.5-5.5, add chitosan-acetic acid stock solution, and continue the reaction at 55℃ for 50 minutes. Adjust the pH to 7.0-7.5, stir, wash, and freeze-dry to obtain purified hydrofluoric acid treated graphene. S2. The graphene obtained in step S1 is immersed in an aqueous solution containing sodium hydroxide and sodium citrate, treated at 75°C for 1 hour, cooled, washed and dried to obtain secondary treated graphene. S3. Disperse the graphene obtained in step S2 in deionized water, adjust the pH to 9.5, add titanate coupling agent, hydrazine hydrate and propylene glycol, and stir for 3 hours; heat to 60°C, add sodium chloroform sulfonate, stir for 20 minutes, filter, wash and dry to obtain a three-stage treated solid phase; S4. Prepare a plating solution containing copper sulfate, 2,2-bipyridine, disodium ethylenediaminetetraacetate, and sodium potassium tartrate. Adjust the pH to 8.5, add the solid phase obtained in step S3, and perform chemical copper plating at 60°C until the reaction is complete. Filter, wash, and dry to obtain a copper-coated phase. S5. The copper-coated phase is mixed with copper powder, pressed into shape, and sintered at 950°C for 2 hours to obtain a highly conductive graphene copper alloy material.
[0006] Furthermore, in step S1, the chitosan-acetic acid stock solution is prepared by dissolving chitosan with a degree of deacetylation of 80-95% in an acetic acid solution.
[0007] Furthermore, in step S1, the final concentration of the boric acid is 0.1-0.5 g / L.
[0008] Furthermore, in step S1, the chitosan-acetic acid stock solution is a gradient chitosan mixed stock solution, which is prepared by mixing chitosan A with a degree of deacetylation ≥95% and a molecular weight of 100-150kDa, chitosan B with a degree of deacetylation 80-95% and a molecular weight of 150-200kDa, and chitosan C with a degree of deacetylation 70-80% and a molecular weight of 200-250kDa in a mass ratio of 70:20:10.
[0009] Furthermore, in step S1, the washing is a gradient temperature washing, using water at 60°C, 55°C, 50°C and room temperature in sequence.
[0010] Furthermore, in step S1, the washing is a gradient temperature washing, using water at 60°C, 55°C, 50°C and room temperature in sequence.
[0011] Furthermore, in step S1, the solid-liquid ratio is 1:25 and the washing time is 5 minutes when washing with hot water at 60°C.
[0012] Furthermore, in step S1, the solid-liquid ratio is 1:30 and the washing time is 5 min when washing with hot water at 55°C.
[0013] Furthermore, in step S1, the solid-liquid ratio is 1:35 and the washing time is 5 minutes when washing with hot water at 50°C.
[0014] Furthermore, in step S1, during washing with room temperature water, the solid-liquid ratio is 1:40, and the time is 5 minutes.
[0015] Furthermore, in step S5, the mass ratio of the copper-coated phase to the copper powder is 2.5:100.
[0016] One or more technical solutions provided in the embodiments of this application have at least the following technical effects or advantages: The synergistic treatment of chitosan and boric acid achieved efficient dual purification of fluoride ions and boric acid residues on the graphene surface, greatly reducing the content of interfacial impurities and avoiding the formation of brittle phases.
[0017] The adsorption and temporary protection of chitosan molecules on the graphene surface repaired the graphene edge defects introduced by chemical treatment, protected the structural integrity of graphene, and thus fully exerted its reinforcing effect.
[0018] By employing a gradient chitosan formulation (with different degrees of deacetylation and molecular weights), a complementary purification and protection system was constructed, making the process insensitive to fluctuations in environmental humidity and significantly improving the stability and repeatability of production.
[0019] The optimized gradient temperature washing process can remove various impurities more precisely and thoroughly, ensuring the cleanliness and consistency of the graphene intermediates and laying a solid foundation for the subsequent formation of a dense copper plating layer.
[0020] The final graphene-copper alloy material exhibits excellent comprehensive performance, possessing both high tensile strength and high thermal conductivity, thus solving the key technical problems of large conductivity loss and unstable performance in existing graphene-copper composite materials. Detailed Implementation
[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to limit the invention; the term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0022] Example 1: A method for preparing a highly conductive graphene / copper alloy material, comprising the following steps: S1. Mix the graphene dispersion and hydrofluoric acid solution at a volume ratio of 50:1, and stir under ultrasonic conditions (power 200W, frequency 10kHz) for 5 minutes. Transfer the mixture to a reaction vessel lined with polytetrafluoroethylene, seal it, heat it to 170 ℃, maintain the temperature for more than 25 hours, and then air cool it to room temperature. Open the reaction vessel, filter the mixture through a microporous membrane, and wash the solid phase once with double-distilled water to obtain a wet filter cake. The graphene concentration in the graphene dispersion is 3 mg / mL, and the HF mass percentage in the hydrofluoric acid solution is 25%. The wet filter cake was redispersed in double-distilled water (solid-liquid mass ratio 1:75), and boric acid was added to a final concentration of 0.1%. Add 0.5 g / L of chitosan and stir at 55°C for 25 minutes; adjust the pH to 4.5-5.5 and add chitosan dropwise. Acetic acid stock solution (chitosan final concentration 0.1) The reaction was continued at 55℃ for 50 min (0.3 g / L); then the pH was adjusted to 7.0-7.5, stirred for 25 min, and then washed five times with double-distilled water at 55℃. The resulting purified hydrofluoric acid-treated graphene was freeze-dried. The chitosan-acetic acid mixture was prepared by dissolving chitosan in acetic acid solution, with a degree of deacetylation of 80-95% and a content of 98%. S2. Prepare an aqueous solution containing 14% sodium hydroxide and 3% sodium citrate by mass. Immerse the purified hydrofluoric acid-treated graphene in the solution at a solid-liquid mass ratio of 1:23, maintain the temperature at 75°C in a water bath, and stir continuously for 1 hour. After air cooling, filter the solution, wash the solid phase with double-distilled water, and freeze-dry to obtain the secondary-treated graphene.
[0023] S3. Disperse the secondary-treated graphene in deionized water at a solid-liquid ratio of 1 mg:3.5 mL, and adjust the pH to 9.5 with 10% sodium hydroxide solution. Add titanate coupling agent (2 mg / 10 mL), hydrazine hydrate (0.5 mg / 10 mL), and propylene glycol (0.3 mg / 10 mL) while stirring, and continue stirring for 3 hours. Then, heat the solution to 60°C in a water bath, add sodium chloroform sulfonate (0.6 mg / 10 mL), and stir for more than 20 minutes. Filter immediately, wash the solid phase with double-distilled water, and freeze-dry to obtain the tertiary-treated solid phase. S4. Prepare two solutions: Solution A: Copper sulfate 12g / L, 2,2 Bipyridine 0.9 g / L; Solution B: Disodium ethylenediaminetetraacetate 8 g / L, potassium sodium tartrate 25 g / L; Mix solution A and solution B by volume ratio of 1:6, and add formaldehyde aqueous solution (37%), methanol aqueous solution (40%) and sodium nitrate aqueous solution (8%), with addition amounts of 15 mL, 7 mL and 5 mL respectively (based on a total volume of 400 mL of mixed solution), to obtain the plating solution.
[0024] The plating solution was kept at a constant temperature of 60℃ in a water bath, and the pH was adjusted to 8.5 with a 10% sodium hydroxide solution. The solid phase that had undergone three treatments was added at a solid-liquid ratio of 0.8 g / L. The solution was stirred and ultrasonically vibrated (100 W power, 10 kHz frequency), and the pH was monitored in real time and maintained at 8.5. When no more bubbles emerged from the plating solution, stirring and vibration were stopped. The solution was then air-cooled and filtered. The solid phase was washed with deionized water and dried at 80℃ to obtain the copper-coated phase. S5. The copper-coated phase and copper powder are mixed at a mass ratio of 2.5:100, pressed into a billet under a pressure of 400MPa, and sintered at 950℃ for 2h to obtain a highly conductive graphene / copper alloy material.
[0025] The synergistic effect of chitosan and boric acid was verified, including a control group and an experimental group. The control group included control group A, control group B, and control group C. Control group A was the original graphene, which was treated with hydrofluoric acid only, without purification steps; control group B was treated with boric acid only (0.3 g / L), without chitosan; control group C was treated with chitosan only (0.2 g / L), without boric acid. The experimental group includes experiments 1-9, as detailed in Table 1. The pH was 5.0 after the addition of boric acid and 7.2 after the addition of chitosan-acetic acid stock solution. The reaction temperature was 55℃ for all experiments. Table 1 Experimental Grouping in Example 1 Experiments were conducted on the different highly conductive graphene / copper alloy materials prepared above, including the detection of residual fluoride ions (ion chromatography), residual boron (inductively coupled plasma mass spectrometry), the degree of graphite defects (Raman spectroscopy, ID / IG ratio, 532 nm), the tensile strength of the composite material (universal testing machine, ASTM E8 standard), and the thermal conductivity of the composite material (laser flare method, ASTM E1461 standard). The results are shown in Table 2. Table 2 Experimental Results of Examples Experimental data show that the synergistic treatment with chitosan and boric acid has significant advantages over single treatment. While control group B (boric acid only) reduced fluorine residue, it increased boron residue, leading to the segregation of new impurities at the copper-graphene interface and the formation of a brittle boride interlayer. In contrast, experimental group 6 (0.3 g / L boric acid + 0.3 g / L chitosan) reduced both fluorine and boron residues, achieving dual purification. This effect stems from chitosan's pH-responsive capture-release mechanism: under acidic conditions (pH 5.0), chitosan amino groups are protonated and bind to boric acid anions via electrostatic interactions; under neutral conditions (pH 7.2), chitosan deprotonates, releasing the bound boric acid complex, which is then removed with the washing solution. This dynamic process maximizes the utilization of boric acid and minimizes residue.
[0026] The changes in the Raman ID / IG ratio revealed the repair effect of chitosan on the graphene structure. Control group A showed that hydrofluoric acid treatment introduced certain defects; experimental group 6 showed that chitosan treatment repaired some defects. Mechanistically, chitosan molecules are adsorbed onto the graphene surface through hydrogen bonds and van der Waals forces. The hydroxyl and amino groups on its polysaccharide chains can interact with dangling bonds at the graphene edges, repairing edge defects. Simultaneously, the temporary protective layer formed by chitosan on the graphene surface prevents mechanical damage and oxidation during subsequent washing and processing; this protective effect was also observed in control group C (chitosan only).
[0027] The clean graphene surface provides uniform nucleation sites for electroless copper plating, enabling the formation of a continuous and dense coating layer during copper ion reduction deposition. The reduction in boron residue prevents boron segregation at the interface, avoiding the formation of a brittle phase and ensuring strong bonding at the copper-graphene interface. Furthermore, the chitosan-repaired graphene structure improves the mechanical and thermal properties of graphene itself, further enhancing the composite material's performance.
[0028] Excessive boric acid, if not fully captured, can become a new source of pollution. This confirms that the synergistic effect of chitosan is not a simple additive effect, but a dynamic balance achieved through its pH-responsive mechanism: an appropriate amount of chitosan can match the amount of boric acid to achieve complete capture; too little will result in insufficient capture, while too much may affect subsequent treatment.
[0029] At the purification level, chitosan's pH-responsive capture-release mechanism enables efficient utilization and complete removal of boric acid. Through the controlled binding and release of chitosan, boric acid can be effectively eluted after completing its fluoride ion complexation task, reducing boron residue by approximately 70%.
[0030] At the structural protection level, the temporary protective layer of chitosan repairs edge defects in graphene and reduces structural damage to graphene during the purification process. This solves the problem of graphene performance degradation that may occur with simple chemical treatment, allowing graphene to fully exert its reinforcing role in composite materials.
[0031] At the process control level, the addition of chitosan makes the purification process more controllable. The purification process can be controlled by adjusting the pH, reducing the difficulty of operation and improving the robustness and repeatability of the process.
[0032] In terms of overall performance, the dual purification process ensures a high degree of cleanliness on the graphene surface, creating ideal conditions for subsequent electroless copper plating. The dense copper coating and strong interfacial bonding ultimately give the composite material excellent mechanical and thermal properties.
[0033] Example 2: The above example, through the designed chitosan synergistic purification steps, fundamentally overcomes the drawback of boric acid introducing boron residue while retaining the advantages of boric acid in removing fluoride, and adds the benefit of graphene structure repair; however, in actual application and production, it was found that the purification effect fluctuates greatly in the high humidity season of summer, and white residue appears on the graphene surface after washing in the low humidity season of winter, and tiny pores appear in the copper plating layer. It was subsequently found that humidity was the factor; therefore, further improvements were made based on Example 1.
[0034] The chitosan used includes: Chitosan A: Degree of deacetylation ≥ 95%, molecular weight range 100-150 kDa; Chitosan B: Degree of deacetylation 80-95%, molecular weight range 150-200kDa; Chitosan C: Degree of deacetylation 70-80%, molecular weight range 200-250kDa.
[0035] Chitosan A, chitosan B, and chitosan C were weighed separately in a mass ratio of 70:20:10 and added to a 1-2% (v / v) aqueous acetic acid solution to prepare a 20 g / L single-component stock solution. The solution was then magnetically stirred (400 r / min) until completely dissolved (approximately 2-3 h) to obtain a gradient chitosan mixed stock solution.
[0036] In step S1, a gradient temperature washing process is also performed. The entire step S1 is as follows: S1. Mix the graphene dispersion and hydrofluoric acid solution at a volume ratio of 50:1, and stir under ultrasonic conditions (power 200W, frequency 10kHz) for 5 minutes. Transfer the mixture to a reaction vessel lined with polytetrafluoroethylene, seal it, heat it to 170 ℃, maintain the temperature for more than 25 hours, and then air cool it to room temperature. Open the reaction vessel, filter the mixture through a microporous membrane, and wash the solid phase once with double-distilled water to obtain a wet filter cake. The graphene concentration in the graphene dispersion is 3 mg / mL, and the HF mass percentage in the hydrofluoric acid solution is 25%. The wet filter cake was redispersed in double-distilled water (solid-liquid mass ratio 1:75), and boric acid was added to a final concentration of 0.3 g / L. The mixture was stirred at 55°C for 25 min. The pH was adjusted to 4.5-5.5, and a graded chitosan stock solution (chitosan final concentration 0.2 g / L) was added dropwise. The reaction was continued at 55°C for 50 min. The pH was then adjusted to 7.0-7.5, and the mixture was stirred for 25 min before washing, specifically including: First wash: 60℃ hot water, solid-liquid ratio 1:25, stir for 5 min; Second wash: 55℃ hot water, solid-liquid ratio 1:30, stir for 5 min; Third wash: 50℃ hot water, solid-liquid ratio 1:35, stir for 5 min; Fourth wash: room temperature water, solid-liquid ratio 1:40, stir for 5 min; Then, freeze-drying is performed to obtain purified hydrofluoric acid-treated graphene; wherein chitosan-acetic acid is prepared by dissolving chitosan in acetic acid solution; Experiments were conducted at humidity levels of 30%, 55%, and 80%, and the results are shown in Table 3. Example 1 used the parameters from Experiment 5 for the experiment.
[0037] Table 3 Experimental Results of Example 2 Example 2 (using gradient chitosan and gradient washing): Under three different humidity environments (30%, 55%, and 80%), key indicators such as fluorine residue, boron residue, ID / IG, tensile strength, and thermal conductivity remained highly consistent with minimal fluctuations. This indicates that the process is not sensitive to environmental humidity.
[0038] Chitosan A (high degree of deacetylation ≥95%, low molecular weight): High degree of deacetylation means more free amino groups, higher protonation at acidic pH, and higher positive charge density. This results in the strongest and fastest electrostatic capture ability for borate anions, ensuring efficient start-up and basic purification effects. Chitosan B (medium degree of deacetylation, medium molecular weight): Balances capture ability and chain length. Its moderate positive charge density and chain length effectively capture borate and form a relatively dense and stable temporary protective layer on the graphene surface, repairing defects and preventing impurity re-adsorption. Chitosan C (lower degree of deacetylation, higher molecular weight): Lower degree of deacetylation may result in slightly different hydrophilicity and chain flexibility; its larger molecular weight allows for the formation of a thicker, more sterically hindered protective layer on the graphene surface. Its main function is to enhance the physical shielding effect on graphene during subsequent washing and processing steps, resisting the adverse effects of environmental humidity fluctuations (such as moisture intrusion at the interface under high humidity and drying stress under low humidity), and improving process robustness.
[0039] The three components are mixed in proportion to form a progressive and complementary system. From rapid purification initiation (A), to efficient purification and structural repair (B), and then to providing long-term stable protection (C), dynamic coverage and full-process stabilization of the purification process are achieved.
[0040] Step 1 (60℃): The higher temperature helps to elute weakly bound physically adsorbed impurities and some chitosan-boric acid complexes, initiating the washing process. Steps 2 and 3 (55℃→50℃): Gradual cooling matches the desorption energy barriers of chemically adsorbed impurities with varying binding strengths, achieving segmented, gentle, and thorough removal of impurities and avoiding graphene sheet stress or agglomeration that may be caused by sudden temperature changes. Step 4 (room temperature): Finally, a room temperature water equilibrium system is used to ensure the removal of all soluble ions and to align the material state with the subsequent process environment (room temperature), reducing surface state changes or residual stress caused by temperature differences.
[0041] Compared to washing at a fixed temperature, it can remove impurities more precisely and thoroughly, and is more adaptable to changes in the hydration state of material surfaces under different humidity conditions, thus ensuring consistent washing results.
[0042] The engineering challenge of "performance instability caused by humidity fluctuations" has been solved: by employing a multifunctional gradient chitosan formulation and an optimized gradient washing process, the sensitivity of the entire purification process to environmental humidity is greatly reduced. Stable, high-performance purification graphene intermediates can be obtained regardless of whether it is a dry winter or a humid summer.
[0043] The "white residue" and coating "porosity" defects in low-humidity environments were eliminated: gradient washing ensured that impurities (possibly unwashed borates or chitosan derivatives) were removed more thoroughly, preventing their precipitation and formation of white residue after drying. A clean surface is a prerequisite for the formation of a dense, porosity-free coating in electroless copper plating. This further enhanced the overall performance ceiling of the final composite material: lower impurity residue, a more complete graphene structure, and a more stable process collectively contributed to superior and more reliable interfacial bonding and material properties, consolidating and slightly improving tensile strength and thermal conductivity compared to the optimal values in Example 1.
[0044] The conductivity of the prepared alloy material was measured (the reference conductivity of copper is 5.8 × 10⁻⁶). 7 S / m (resistivity 1.72×10) -8 The alloy material obtained in Example 1 (Experiment 5) had an electrical conductivity of 5.4 ± 0.2, which is 93.1% of the conductivity of copper, and a resistivity of 1.85 ± 0.07 × 10⁻⁶ Ω·m. -8 Ω·m; The alloy material obtained in Example 2 has an electrical conductivity of 5.7 ± 0.2, which is 98.3% of the conductivity of copper, and a resistivity of 1.75 ± 0.07 × 10⁻⁶ Ω·m; -8 Ω·m; Boric acid effectively complexes fluoride ions, reducing the formation of fluorides at the interface and decreasing interfacial resistance. When using gradient chitosan and gradient cooling, it guides the copper layer to deposit in a more ordered manner, reducing electronic wavefunction mismatch at the interface, lowering the quantum tunneling barrier, and the extremely low boron residue reduces the solid solution of boron in the copper lattice, resulting in better copper lattice integrity and an increased mean free path of electrons.
[0045] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. For those skilled in the art, the present invention can have various modifications and variations. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a highly conductive graphene / copper alloy material, characterized in that, Includes the following steps: S1. Graphene dispersion and hydrofluoric acid solution were mixed at a volume ratio of 50:1 and ultrasonically treated for 5 minutes. The mixture was then placed in a reaction vessel and kept at 170°C for 25 hours. After cooling, it was filtered and washed to obtain a wet filter cake. The wet filter cake was redispersed in double-distilled water, boric acid was added, and the mixture was stirred at 55°C for 25 minutes. The pH was adjusted to 4.5-5.5, chitosan-acetic acid stock solution was added, and the reaction continued at 55°C for 50 minutes. The pH was adjusted to 7.0-7.5, and the mixture was stirred, washed, and freeze-dried to obtain purified hydrofluoric acid-treated graphene. The washing was performed using gradient temperature washing, successively with water at 60°C, 55°C, 50°C, and room temperature. The chitosan-acetic acid stock solution is a gradient chitosan mixed stock solution, which is prepared by mixing chitosan A with a deacetylation degree ≥95% and a molecular weight of 100-150kDa, chitosan B with a deacetylation degree of 80-95% and a molecular weight of 150-200kDa, and chitosan C with a deacetylation degree of 70-80% and a molecular weight of 200-250kDa in a mass ratio of 70:20:
10. The final concentration of the boric acid is 0.1-0.5 g / L; S2. The graphene obtained in step S1 is immersed in an aqueous solution containing sodium hydroxide and sodium citrate, treated at 75°C for 1 hour, cooled, washed and dried to obtain secondary treated graphene. S3. Disperse the graphene obtained in step S2 in deionized water, adjust the pH to 9.5, add titanate coupling agent, hydrazine hydrate and propylene glycol, and stir for 3 hours; heat to 60°C, add sodium chloroform sulfonate, stir for 20 minutes, filter, wash and dry to obtain a three-stage treated solid phase; S4. Prepare a plating solution containing copper sulfate, 2,2-bipyridine, disodium ethylenediaminetetraacetate, and sodium potassium tartrate. Adjust the pH to 8.5, add the solid phase obtained in step S3, and perform chemical copper plating at 60°C until the reaction is complete. Filter, wash, and dry to obtain a copper-coated phase. S5. The copper-coated phase is mixed with copper powder, pressed into shape, and sintered at 950°C for 2 hours to obtain a highly conductive graphene copper alloy material.
2. The preparation method according to claim 1, characterized in that, In step S5, the mass ratio of the copper-coated phase to the copper powder is 2.5:100.
Citation Information
Patent Citations
Preparation method of graphene-copper composite material
CN112593108A
Graphene conductive paste for battery and preparation method of graphene conductive paste
CN117317231A
Synthetic method of difluoromethyl triazolinone intermediate capable of reducing fluorine ion content
CN117777034A